Lean construction as a panacea for poor construction projects performance - William Nkeonyeasua Nwaki; Chidiebere Emmanuel Eze (ITEGAM-JETIA, 2020)
Recurring problems in the delivery of construction projects have been time and cost overruns, poor quality, poor health and safety, waste and loss of value. This situation is worsened by the reluctance of construction organisations to fully implement lean construction technique which has proved to be an innovative solution to these problems. This study assessed construction professionals’ perception of the awareness, adoption and benefits of lean construction in remedying poor construction project performance in the south-south region of Nigeria. A well-structure questionnaire distributed by hand and electronically using the snowball sampling technique were used to gather data from the participants from both the private and public organisations. Frequency, percentage and factor analysis were used to analyse the collected data. It was found that the level of awareness of lean construction is high but it s adoption is low. Lean construction is a panacea for poor construction project performance because of it s cost related benefits, value and relationship benefits, environmental benefits, quality improvement benefits, motivation and productivity benefits, profitability and market benefits, time and work flow benefits, waste reduction benefits, and HS and rework reduction benefits. The creation of dedicated department/team for driving the lean initiative is recommended.